Phosphoserine Lyase Deoxyribozymes: DNA-Catalyzed Formation of Dehydroalanine Residues in Peptides - Chandrasekar, Jagadeeswaran (J Am Chem Soc, 2015)
Dehydroalanine (Dha) is a nonproteinogenic electrophilic amino acid that is a synthetic intermediate or product in the biosynthesis of several bioactive cyclic peptides such as lantibiotics, thiopeptides, and microcystins. Dha also enables labeling of proteins and synthesis of post-translationally modified proteins and their analogues. However, current chemical approaches to introducing Dha into peptides have substantial limitations. Using in vitro selection, here we show that DNA can catalyze Zn(2+) or Zn(2+)/Mn(2+)-dependent formation of Dha from phosphoserine (pSer), i.e., exhibit pSer lyase activity, a fundamentally new DNA-catalyzed reaction. Two new pSer lyase deoxyribozymes, named Dha-forming deoxyribozymes 1 and 2 (DhaDz1 and DhaDz2), each function with multiple turnover on the model hexapeptide substrate that was used during selection. Using DhaDz1, we generated Dha from pSer within an unrelated linear 13-mer peptide. Subsequent base-promoted intramolecular cyclization of homocysteine into Dha formed a stable cystathionine (thioether) analogue of the complement inhibitor compstatin. These findings establish the fundamental catalytic ability of DNA to eliminate phosphate from pSer to form Dha and suggest that with further development, pSer lyase deoxyribozymes will have broad practical utility for site-specific enzymatic synthesis of Dha from pSer in peptide substrates.